Design of Multicationic Copper‐Bearing Layered Double Hydroxides for Catalytic Application in Biorefinery. Issue 6 (28th February 2023) - Awan, Iqra Zubair; Ho, Phuoc Hoang; Beltrami, Giada; Gimello, Olinda; Cacciaguerra, Thomas; Gaudin, Pierrick; Tanchoux, Nathalie; Albonetti, Stefania; Martucci, Annalisa; Cavani, Fabrizio; Tichit, Didier; Di Renzo, Francesco
Abstract: Ethanol has been used as a renewable hydrogen‐donor in the conversion of a lignin model molecule in subcritical conditions. Noble metal‐free porous mixed oxides, obtained by activation of Cu−Ni−Al and Cu−Ni−Fe layered double hydroxide (LDH) precursors, have been used as heterogeneous catalysts for Meerwein‐Ponndorf‐Verley (MPV) hydrogen transfer and further hydrogenation by ethanol dehydrogenation products. Both the Cu/(Cu+Ni) ratio and the nature of the trivalent cation (Al or Fe) affect the activity of the catalysts, as well as the selectivity towards the different steps of the hydrogenation reactions and the cleavage of lignin‐like phenylether bonds. Accounting for the peculiar behaviour of Cu 2+ and M(III) cations in the synthesis of LDHs, the coprecipitation of the precursors has been monitored by titration experiments. Structural and textural properties of the catalysts are closely related to the composition of the LDH precursors. Abstract : Catalysis in biorefineries : Organosolv pulping performs fractionation of lignocellulose with recuperation of lignin. Is it possible to start depolymerisation and hydrodeoxygenation of lignin already in pulping, by using the solvent as hydrogen‐donor? Copper catalysts are effective and coupled with nickel preserve useful aromatic rings. Hurdles in catalyst preparation (difficult precipitation of mixed copper hydroxides and ease of formation of mixed spinels) have been addressed.